Origin of Enhanced Photoelectrochemical Activity of the n-CdS/p-type Semiconductor Interface: Homojunction or Heterojunction? - Chae, Sang Youn; Jun, Minki; Yoon, Noyoung; Joo, Oh Shim; Kim, Jin Young; Park, Eun Duck (Small, 2025)
Surface engineering of photoelectrodes is considered critical for achieving efficient photoelectrochemical (PEC) cells, and various p-type materials have been investigated for use as photoelectrodes. Among these, the p-type semiconductor/n-type CdS heterojunction is the most successful photocathode structure because of its enhanced onset potential and photocurrent. However, it is determined that the main contributor to the enhanced activity is the Cd-doped layer and not the CdS layer. In this study, a Cd-doped n+p-buried homojunction of a CuInS2 photocathode is first demonstrated without a CdS layer. The homojunction exhibited a more active and stable PEC performance than the CdS/CuInS2 heterojunction. Moreover, it is confirmed that Cd doping is effective for other p-type materials. These results strongly suggest that the effects of Cd doping on photocathodes should be carefully investigated when designing CdS/p-semiconductor heterojunction photoelectrodes. They also indicate that the Cd-doped layer has great potential to replace the CdS layer in future photoelectrode designs.
Keywords: Cd-doped; CdS; CdS layer; CuInS 2; Doped layers; Homo-junctions; P type semiconductor; P-type; Photoelectrochemicals; Photoelectrode; CdS; CuInS2; Doping; Homojunctions; Photoelectrodes